Only the strong : reversing the Left's plot to sabotage American power - Cotton, Tom (Twelve, 2022)
A New York Times best-selling author and conservative U.S. Senator reveals the untold inside story of how progressive ideologues and Democratic politicians abandoned the American tradition of strength, pride and honor, providing a formidable and urgent roadmap to restore American strength before it's too late.